2014
DOI: 10.7554/elife.03497
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary consequences of intra-patient phage predation on microbial populations

Abstract: The impact of phage predation on bacterial pathogens in the context of human disease is not currently appreciated. Here, we show that predatory interactions of a phage with an important environmentally transmitted pathogen, Vibrio cholerae, can modulate the evolutionary trajectory of this pathogen during the natural course of infection within individual patients. We analyzed geographically and temporally disparate cholera patient stool samples from Haiti and Bangladesh and found that phage predation can drive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 29 publications
7
128
0
Order By: Relevance
“…The conjugation efficiency was calculated as the number of transconjugants per donor. (27) and Bangladesh (37), we found that this CRISPR-Cas system is strictly limited to classical biotype strains (Table 2). Detailed analysis of the spacer composition of classical biotype strains was not possible due to the repetitive nature of the CRISPR array and the relatively low sequence coverage obtained in the previous study (4).…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…The conjugation efficiency was calculated as the number of transconjugants per donor. (27) and Bangladesh (37), we found that this CRISPR-Cas system is strictly limited to classical biotype strains (Table 2). Detailed analysis of the spacer composition of classical biotype strains was not possible due to the repetitive nature of the CRISPR array and the relatively low sequence coverage obtained in the previous study (4).…”
Section: Methodsmentioning
confidence: 78%
“…Two notable examples include the introduction of cholera toxin, which is encoded by a lysogenic filamentous phage (50), and the SXT/R391 integrated conjugative elements, which have been key drivers of antibiotic resistance since the early 1990s (4). The potential barrier to sampling such elements imposed by CRISPR-Cas may have had too great a cost, and the system may have been lost in seventh pandemic isolates, despite the need for protection from prevalent lytic phages in the host and the environment (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for frequent receptor mutation follows from increases in the numbers of nonsynonymous mutations in phage receptors (10) and adaptive receptor mutations in response to phage in natural populations (11); a study on the human pathogen Vibrio cholerae showed that in response to phage, bacteria acquired point mutations in the outer membrane porin OmpU, the receptor for the lytic phage ICP2 (11). Many phages of Gram-negative bacteria use outer membrane lipopolysaccharides (LPSs) to enter the host cell, which are macromolecules consisting of a lipid and a polysaccharide group.…”
Section: Surface Modificationmentioning
confidence: 99%
“…Indeed, phage-mediated control of Flavobacterium psychrophilum, a fish pathogen, resulted in surface mutants with attenuated virulence (246). The human pathogen Vibrio cholerae lost the ability to spread between patients after it acquired a surface mutation that conferred resistance against phage (11), and an E. coli strain infecting calves had greatly reduced virulence following resistance evolution (247). Hence, understanding the conditions under which different types of resistance evolve may therefore be important for predicting pathogen virulence, particularly in light of the resurgent interest in the therapeutic use of phages.…”
Section: Broader Consequences Of Different Immune Mechanismsmentioning
confidence: 99%